Sodium bicarbonate to prevent cardiac surgery-associated kidney injury: the end of a dream? - Hougardy, Jean-Michel (BioMed Central, 2012)
The rationale of urine alkalinization through intravenous sodium bicarbonate to prevent cardiac surgery-associated acute kidney injury relies on several pathophysiological arguments. Urine alkalinization is easily feasible in the ICU setting and is often considered to be associated with few side effects. In a previous issue of Critical Care, a retrospective study evaluates the effect of routine intravenous bicarbonate use to prevent cardiac surgery-associated acute kidney injury with cardiopulmonary bypass. This commentary discusses recent data on the use of bicarbonate to prevent cardiac surgery-associated acute kidney injury.